The impact of financial stability between the linkages of awareness and environmental tax compliance - Norsiah, Ahmad; Nik Mohd Norfadzilah, Nik Mohd Rashid; Juhaida, Abd Ghani (2019)
Environmental concern has been given serious attention after the government launched the cleanliness campaign in 1982. The main purpose of the campaign is to awaken citizen about the importance to preserve and conserve the environment due to fluctuation of environmental problem, particularly environmental pollution. Until now, our government had introduced some campaign through ‘green incentives’ to green practitioners. Newly, our government has allocated few million Ringgits to those states that practices and built ‘green’ in Budget 2019. However, the pollution statistics shows fluctuation in year 2015 and 2016 and seems the government programmes is not fully effective. Accordingly, this study attempts to investigate the impact of financial stability towards the linkage of environmental awareness and environmental tax compliance. This study only consists 384 tourists in East Coast Malaysia. Data collected using questionnaires. The results indicate a positive and significant difference between low and high financial stability. The results of this study make a contribution to existing literature in the area of environmental awareness and tax compliance. In addition, this research adds further evidence to the value of studying environmental tax.